Role of citicoline in improvement of cognition, memory and post stroke disability in stroke patients - Singh, Mahendrapal; Khan, Mohd. Imran; Giri, Richa; Kumar, Lalit (International Journal of Advances in Medicine, 2019)
Background: Citicoline has emerged as a potential neuroprotectant in experimental models in stroke patients. Citicoline has shown some beneﬁcial effects in human ischaemic stroke and with an excellent safety proﬁle while in haemorrhagic stroke data is limited. Authors conducted this study to test role of citicoline in stroke patients in terms of cognition, memory and post stroke disability. Methods: In this prospective study, patients had to be previously independent, aged >18 years of age, presented within 24 hours of onset of symptoms of stroke diagnosed by neuroimaging (CT or MRI). Patients received either a placebo or 500 mg/12 h citicoline for 12 weeks (orally or intravenously). The primary aim was to evaluate improvement in cognition, memory and post stroke disability after 12 weeks. The efﬁcacy endpoint was the percentage of subjects with MMSE and DRS at 12 weeks. Results: Total 75 stroke patients were enrolled, 40 in control group and 35 in citicoline group were allotted randomly. Patients in citicoline group were given intravenous citicoline 500 mg/12 hour during hospital stay and orally 500 mg/12 hour after discharge for up to 12 weeks. Control Group was given Placebo. cognition, memory and post stroke disability show positive improvement in citicoline group. Conclusions: Citicoline shows beneficial effects in stroke in terms of cognition, memory and post stroke disability.